2019
DOI: 10.1186/s12868-019-0532-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of PI3K-mediated AMPA receptor changes in post-conditioning of propofol in brain protection

Abstract: Background We aimed to study the role of amino-3-hydroxy-5-methylisoxazole-4-propionic acid receptor (AMPAR) glutamate receptor 2 (GluR2) subunit trafficking, and activity changes in short-term neuroprotection provided by propofol post-conditioning. We also aimed to determine the role of phosphoinositide-3-kinase (PI3K) in the regulation of these processes. Methods Rats underwent 1 h of focal cerebral ischemia followed by 23 h of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…As an anesthetic, PPF has the same neuroprotective properties as other general anesthetics. PPF post-conditioning alleviates transient MCAO in rats by exerting the acute neuroprotective effects . PPF promotes PTEN degradation, which contributes to reducing hippocampal neuronal loss and memory deficit in CI/R injury rats .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an anesthetic, PPF has the same neuroprotective properties as other general anesthetics. PPF post-conditioning alleviates transient MCAO in rats by exerting the acute neuroprotective effects . PPF promotes PTEN degradation, which contributes to reducing hippocampal neuronal loss and memory deficit in CI/R injury rats .…”
Section: Resultsmentioning
confidence: 99%
“…PPF post-conditioning alleviates transient MCAO in rats by exerting the acute neuroprotective effects. 22 PPF promotes PTEN degradation, which contributes to reducing hippocampal neuronal loss and memory deficit in CI/R injury rats. 23 Our study also confirmed the neuroprotective effect of PPF in CI/R injury through the SNHG14/ miR-30b-5p/Atg5/Beclin 1 axis.…”
Section: ■ Introductionmentioning
confidence: 98%
“…23 In addition, the activation of PI3K/AKT/CREB signalling pathway is positively associated with the neuroprotective function that can cause neonatal hypoxia ischaemia. 7,19,31 Furthermore, CREB is a protein that controls gene transcription and affects the regulation of downstream caspase 3 gene transcription and protein translation. Besides, its active form is a key factor in memory formation and the normal development of neurons (Figure 6G).…”
Section: Discussionmentioning
confidence: 99%
“…The mature BDNF binds to TrkB so as to activate the downstream signalling pathways responsible for regulating gene expression encoding proteins involved in neural cell survival, axon and dendrite growth, as well as synapsis plasticity 23 . In addition, the activation of PI3K/AKT/CREB signalling pathway is positively associated with the neuroprotective function that can cause neonatal hypoxia ischaemia 7,19,31 . Furthermore, CREB is a protein that controls gene transcription and affects the regulation of downstream caspase 3 gene transcription and protein translation.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthesia management includes the choice of anesthetic and the management of intraoperative circulation. Many anesthetics have protective effects on the brain, 8 , 9 , 10 but there are few reports about the effects of anesthetics on patients with a history of stroke. The operation requires electrophysiology to find the C7 nerve accurately.…”
Section: Anesthesia Managementmentioning
confidence: 99%